Perilaku Penelusuran Informasi Generasi Z dalam Memenuhi Kebutuhan Informasi di perpustakaan UIN Raden Fatah Palembang - Ahmad Wahidi; Ardi Prasetio (Dinasti Research, 2025)
This study aims to identify and analyze the information search behavior of generation Z in meeting information needs at the UIN Raden Fatah Palembang Library. Generation Z, known as the digital generation, has unique characteristics in the way they search for and use information. The method used in this study is a descriptive qualitative approach, with data collection through in-depth interviews and observations. The results of the study indicate that generation Z tends to rely on electronic devices such as smartphones and laptops to access information through online catalogs and academic databases. However, they also use physical resources such as books, although in smaller quantities.